Rain and Plants: Study of Takhrij and Syarah Hadith on Agrotechnology - Muhamad Rizky Septian Kurnia; Tuti Garnasih; Kifah Gibraltar Bey Fananie; Nurul Azizah (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet Muhammad ï·º with regard to photosynthesis. This research method is a qualitative type through literature and field studies with the takhrij and syarah hadith approaches. Results and discussion of this research. Photosynthesis is a biochemical process. Carbohydrate recipes from inorganic materials are carried out by plants, especially plants that contain green leaves, namely chlorophyll. Rainfall affects the growth process and production of food crops. This is because the rain produces air which is useful as a transport of nutrients from the soil to the roots of plants to show them to other parts.